1996
DOI: 10.1007/bf02437906
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and gender differences in sexuality: Variations in sexual behavior between Asian and non-Asian university students

Abstract: Seven hundred and two (346 non-Asian, 356 Asian) undergraduate volunteers were assessed in a confidential laboratory setting on levels of interpersonal sexual behavior (e.g., petting, intercourse), intrapersonal sexual behavior (e.g., fantasy, masturbation), and sociosexual restrictiveness (e.g., lifetime number of partners, number of "one-night stands"). The purpose was to examine possible differences in sexual behavior between Asian and non-Asian Canadian university students and to determine the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 60 publications
10
78
2
Order By: Relevance
“…However, the frequencies of men and women in terms of losing virginity and gender differences in age at first intercourse vary across cultures (see Higgins et al, 2002;Kupek, 2001;Meston et al, 1996;Ozan et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the frequencies of men and women in terms of losing virginity and gender differences in age at first intercourse vary across cultures (see Higgins et al, 2002;Kupek, 2001;Meston et al, 1996;Ozan et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Men have been much more likely than women to report that they have engaged in sexual intercourse (Herald, Valenzuala, & Morris, 1992;Meston et al, 1996).…”
Section: Sexual Attitudes and Behaviorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies conducted in South East Asian countries have shown that premarital sex is common among youth and mostly occur between partners of romantic relationships (6,7). It has also been noted that sexual relations that occur within romantic relationships are not always consensual.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Asian cultures, short term and long term negative consequences of premarital sexual behaviour, both physical and emotional, have been found to be more in women. Gender inequality and the imbalance of power have been cited as playing a crucial part in coercive and abusive sexual behaviour within romantic relationships between males and females (7). Attitudes of young people on gender roles are cited as a powerful mediator of their expressions of sexuality and to be an underlying determinant of sexual behaviour (8).…”
Section: Introductionmentioning
confidence: 99%